- -
Solved Examples
Click on a 'View Solution' below for other questions:
c   If y = 9x + 5cos-1x, then dydx =   c View Solution
c   If y = 2x + 3sin-1x, then dydx =   c View Solution
c   If y = sin-1(cos 23x), x (0 , π) then, find dydx .   c View Solution
e   If y = 2cos-1(sin 4x), x (- π2, π2), then dydx =
   e
View Solution
e   If y = sin-1(8xa), a > 0, then y′ =
   e
View Solution
e   If y = cos-1(8xx+3), then y′ =
   e
View Solution
e   If y = tan-1(cos 8x1 + sin 8x), then y′ =   e View Solution
e   y = tan-1(ln 3x). What is y′?
   e
View Solution
e   If y = cos-1(3x + 5), then find dydx.
   e
View Solution
e   If y = ecot-1x6, then y′ is   e View Solution
e   y = (cos-14x )(tan-14x). Find y   e View Solution
e   If y = 9x sec-13x, x > 1, then y′ =
   e
View Solution
e   If y = 8xsin-12x, then find y′
   e
View Solution
e   If y = 4(tan-12x)2, then y′ =   e View Solution
e   If y = ecos-1(x + 2), then y′ = ?
   e
View Solution
e   If y = tan-1 (4x1+1-16x2), then find y′.
   e
View Solution
e   If y = 8cos-1(4x3 - 3x), then y′ =
   e
View Solution
e   Find the first derivative of 58tan-1[6x - 8x31 - 12x2] with respect to 29tan-1[4x1 - 4x2].   e View Solution
e   If y = sin-15x + sin-1 1 - 25x2 + 36x, then y′ = ?   e View Solution
e   Find the derivative of 48tan-1[10x1 - 25x2] w.r.t 47sin-1[10x1 + 25x2].
   e
View Solution
e   If y = tan-1[1+16x2 -1-16x21+16x2 +1-16x2], then dydx = ?   e View Solution
e   If y = 17x - 6cot -1x, then dydx =?   e View Solution
e   If y = 9sin-19x - 5cos-19x, then find y′.   e View Solution
e   If y = 25sin-1(3x3), then y′ =?
   e
View Solution
e   If y = 24xsin-14x + 91-x2, then y′ = ?
   e
View Solution
e   If y = sin-1(cos 41x), x (0 , π) then, find dydx .   e View Solution
e   If y = 2cos-1(sin 2x), x (- π2, π2), then dydx =
   e
View Solution
e   If y = 8x + 2cos-1x, then dydx =   e View Solution
e   If y = 3x + 2sin-1x, then dydx =   e View Solution
e   If y = cos-1(2xx+3), then y′ =
   e
View Solution
e   If y = sin-1(9xa), a > 0, then y′ =
   e
View Solution
e   If y = tan-1(cos 16x1 + sin 16x), then y′ =   e View Solution
e   y = tan-1(ln 9x). What is y′?
   e
View Solution
e   y = (cos-13x )(tan-19x). Find y   e View Solution
e   If y = 2x sec-12x, x > 1, then y′ =
   e
View Solution
e   If y = cos-1(5x + 3), then find dydx.
   e
View Solution
e   If y = ecot-1x4, then y′ is   e View Solution
e   If y = ecos-1(x + 5), then y′ = ?
   e
View Solution
e   Find dydx, if y = sin- 1 x.
   e
View Solution
e   If y = 3xsin-12x, then find y′
   e
View Solution
e   If y = 2(tan-12x)2, then y′ =   e View Solution
e   If y = 9cos-1(4x3 - 3x), then y′ =
   e
View Solution
e   Find the first derivative of 196tan-1[18x - 216x31 - 108x2] with respect to 49tan-1[12x1 - 36x2].   e View Solution
e   If y = tan-1 (6x1+1-36x2), then find y′.
   e
View Solution
e   If y = sin-15x + sin-1 1 - 25x2 + 42x, then y′ = ?   e View Solution
e   Find the derivative of 35tan-1[4x1 - 4x2] w.r.t 34sin-1[4x1 + 4x2].
   e
View Solution
e   If y = 4sin-14x - 4cos-14x, then find y′.   e View Solution
e   If y = 31sin-1(2x3), then y′ =?
   e
View Solution
e   If y = tan-1[1+49x2 -1-49x21+49x2 +1-49x2], then dydx = ?   e View Solution
e   If y = 49x - 8cot -1x, then dydx =?   e View Solution
e   If y = 41xsin-13x + 31-x2, then y′ = ?
   e
View Solution
e   Find dydx, if y = cos- 1 x.   e View Solution
e   If y = tan- 1 x, then find dydx.   e View Solution
e   If y = cot- 1 x, then find dydx.   e View Solution
e   If y = sec- 1 x, then find dydx.   e View Solution